SOCIAL ACTIVITY OF THE SUBJECTIVE MIDDLE CLASS OF THE RUSSIAN REGION: RESULTS OF QUALITATIVE SOCIOLOGICAL RESEARCH - E. , Svetlana; Sazonova, Polina V. (International Journal of Psychosocial Rehabilitation, 2020)
The article presents the results of a study of the middle class of the Russian region in terms of the manifestation of various types of social activity by actors. The emphasis on the analysis of social activity is motivated by the consideration of this attribute as a criterion for the allocation of the middle class in the post-industrial period. The research method – an in-depth focused interview through which two tasks are solved: identifying the degree of significance for informants of social activity and examples of its manifestation; determination of the degree of readiness to participate in the implementation of the innovation development strategy of the Tomsk Region and thereby act as a “driver” of social changes. Representatives of the middle class are included in the sample based on self-identification. It was revealed that the middle class of the Russian region is active in realising personal, but not social goals. Such a characteristic of the post-industrial middle class as the willingness to act as a driver of social development is not observed. Based on the results of the study, options are proposed for solving this problem related to the mechanisms of involving the middle class in regional planning and decision-making regarding generally significant issues.